Visualizing the Keris through a Documentary Video: A Initiative to Raise Awareness Among the Youth of Aeng Tong-Tong Village about the Keris of Sumenep - Ahmed David Anugerah; Ahmad Walid Hujairi; Syamsul Arifin; Ach. Andiriyanto; Ahmad Ghufrony; Rachmad, Teguh Hidayatul (LPPM Stikosa - AWS, 2023)
Aeng Tong-tong Village, Saronggi District, Sumenep Regency is one of the villages that has the largest keris craftsmen in the world. However, it was recently discovered that the participation of village youth in preserving keris was starting to erode and they did not have a good level of concern, which can be seen from their participation in keris craft activities which continued to fade. Based on this problem formulation, this research focuses on the visualization of keris in the form of video documentaries as a new approach to increasing awareness of the youth of Aeng Tong-tong Village towards keris crafts. This research uses a development method that is oriented towards the development of a product whose development process is described carefully through a documentary video product. The results of this research show 1) Documentary video as a medium for socializing the value of the Sumenep keris, 2) Documentary video as a medium of learning and knowledge, 3) Keris documentary video as a means of motivating village youth, 4) Documentary video as a media empowerment innovation.